Blinded by the light: Seabird collision events in South Georgia - Jamie Coleman; Philip R. Hollyman; Andy Black; Martin A. Collins (Polar Biology, 2022)
Light-induced bird strikes on vessels occur frequently in association with areas of high seabird density, often resulting in bird mortalities. These incidents are poorly understood and likely under-reported by vessels. Here we present the details of four separate bird strike events (899, 206, 50 and 47 birds), which took place whilst vessels (two fishing trawlers and one tourist expedition ship) were navigating along the south coast of South Georgia, and discuss possible contributing factors. All species encountered in these events were burrowing petrel species in the family Procellariidae, with diving-petrel species ( Pelecanoides spp.) being most commonly reported. All four events took place during the night in similar meteorological conditions, with poor visibility due to fog, light precipitation and low wind speeds. We identify the waters off the south coast, between King Haakon Bay and Drygalski Fjord, which have remained rat free and are of exceptional importance to breeding seabirds, as high risk for collisions and propose other high-risk areas. The different mortality rates recorded during these events are likely attributed to the varying actions taken by ship crew and persons on board. We propose actions that will help reduce the occurrence of events and mitigate the impact of bird strikes, including the avoidance of high-risk areas in certain night-time conditions. We give recommendations on what to do when birds land on board and stress the importance of reporting of events. Given the expected increase of both fishing and tourist ship activity in South Georgia waters, there is an increasing need to understand and mitigate this threat to seabirds.